Factors Associated with Musculoskeletal Disorders of Soppeng District Population and Civil Registration Services - Syatriani, Sri; Windasari, Dewi Purnama; Amaliah, Umrah Nur’ (Indonesian Journal of Global Health Research, 2024)
Musculoskeletal disorders are problems that cause discomfort in striated muscles, joints and other soft tissues ranging from mild to severe complaints. According to WHO in 2021, around 1.71 billion people have Musculoskeletal Disorders (MSDs) worldwide. Musculoskeletal conditions are the leading cause of disability worldwide with low back pain being the leading cause of disability in 160 countries. This study aims to determine the association between sitting position, body mass index, and working period with musculoskeletal disorders. This research is an analytical research with a cross sectional study design. The population is all computer workers with a sample size of 45 respondents using total sampling. The measuring tools used are the Nordic Body Map (NBM) and the Rappid Office of Strain Assessment (ROSA). The statistical test used is the Fisher exact test. The results of the study showed that there was a association between sitting position (p=0.033<0.05), body mass index (p=0.031<0.05) and working period (p=0.023<0.05) with musculoskeletal disorders. The conclusion of the research is that there is a association between sitting position, body mass index and working period with musculoskeletal disorders of Soppeng Regency Population and Civil Registration Services employees.